Design of a Service and Role-Based Performance Assessment System to Support Employee Performance Assessment - Fadhilah, M Rizki; Yastica, Tiara Verita; Gunawan, Hendra (IT Journal Research and Development, 2022)
The challenge that is often faced by companies is how to find solutions that can be used to evaluate the performance of their employees. The purpose of this study is to design a service-based performance appraisal system with a ticket system to support employee performance appraisals in a company. By using this service-based assessment system, performance appraisal can be carried out objectively based on what the employees have done, this is possible because the parts and roles in the company have been mapped, where each role has different services to handle. As the employee has finished doing certain services, the employee will get points according to what has been done. At the end of each month, the company can determine the "Best Employee of the Month" based on the total point data obtained in a certain month, then the appropriate reward or punishment can be given based on their performance.